Cervejas panfletárias : os discursos politizados de cervejarias independentes brasileiras no ambiente virtual - Teixeira, Fernanda de Moura (2022)
Beer is popularly known as one of the greatest passions of the Brazilian people. The expansion of craft beers in the last decade, expressively in Brazil, has significantly transformed the national beer market and consumer habits in all its plurality. Not only new gustatory ranges are perceived, but also social provocations coming from a common denominator: the beer producer. Rethought by nano and microbreweries, beer complexifies its meaning beyond a marketing product, but also of sociocultural relevance. The purpose of this study is to analyze the discourses and their production of meaning from independent breweries that support as brand positioning three social agendas widely debated today: the black movement, the criticism of the federal government and the feminism. The guidelines are represented in this study by the corpus clipping that delimits three breweries: Implicantes, Mito and Sapatista. To fulfill this purpose, the investigation, of a qualitative and exploratory nature, proposes a methodological course organized in two stages: the first one is supported by bibliographic and documentary research and the second one develops the interpretation of data based on the French Discourse Analysis. The unfolding of these stages results in five sections: the first explores the consumption of goods and images (DEBORD, 2007; BAUMAN, 2008; CANCLINI, 2010); the second encompasses new advertising practices based on new media and stresses these conditions with the social character of technology (WOTTRICH, 2018; 2019; TÔRRES DE AZEVEDO; ATEM, 2019; SHIRKY, 2011); the third debates the media discourse supported by the French School's Discourse Analysis, updating contemporary reflections necessary for the understanding of the central concepts (MAINGUENEAU, 2015; BAKHTIN, 2003; CHARAUDEAU, 2004; 2005; 2009; 2010); the fourth is dedicated to the object of research, deepening the socio-historical economic context of beer in Brazil and in the world, debating the relationship between the environment and the political ethos and mapping the breweries of political positioning explored in his Communication (HALES, 2010; MORADO, 2017; KROHN, 2017). Finally, in the fifth section, the discourse analysis takes place in a corpus of 8 posts made between the three selected brands, during the year 2021, in which deepened understandings about the “politicized discourses of Brazilian independent breweries in the virtual environment” are made. As main results, it is evident that breweries articulate and organize strategies based on a common discourse among independent breweries, which exalts the small producer and brewing diversity. They use aesthetics and the word as a way to make an impact, exploring the ideals they believe in, and considering the reality of interaction that charges the virtual environment, debate and reflect on it. The three brands analyzed have points in common, but also different. There are independent breweries that intensify their discourse even in a polarized way, and breweries that speak their agendas in parallel with an entrepreneurial sales logic in search of space in the job market, recognition and identity promotion. Thus, there is media scheduling, sometimes the intersection of problematizations and the return to certain social commitments.